Practical Gammatone-Like Filters for Auditory Processing - R. F. Lyon; E. M. Drakakis; A. G. Katsiamis (EURASIP Journal on Audio, Speech, and Music Processing, 2007)
This paper deals with continuous-time filter transfer functions that resemble tuning curves at particular set of places on the basilar membrane of the biological cochlea and that are suitable for practical VLSI implementations. The resulting filters can be used in a filterbank architecture to realize cochlea implants or auditory processors of increased biorealism. To put the reader into context, the paper starts with a short review on the gammatone filter and then exposes two of its variants, namely, the differentiated all-pole gammatone filter (DAPGF) and one-zero gammatone filter (OZGF), filter responses that provide a robust foundation for modeling cochlea transfer functions. The DAPGF and OZGF responses are attractive because they exhibit certain characteristics suitable for modeling a variety of auditory data: level-dependent gain, linear tail for frequencies well below the center frequency, asymmetry, and so forth. In addition, their form suggests their implementation by means of cascades of N identical two-pole systems which render them as excellent candidates for efficient analog or digital VLSI realizations. We provide results that shed light on their characteristics and attributes and which can also serve as Ã¢Â€Âœdesign curvesÃ¢Â€Â for fitting these responses to frequency-domain physiological data. The DAPGF and OZGF responses are essentially a Ã¢Â€Âœmissing linkÃ¢Â€Â between physiological, electrical, and mechanical models for auditory filtering.